2011
DOI: 10.1097/bsd.0b013e3182060337
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical Outcomes of Lenke Type 1 Idiopathic Scoliosis

Abstract: In treating thoracic scoliosis, the VCA technique could achieve as good correction and clinical outcome as the derotation technique. The advantage lies in its superior renormalization effect of thoracic kyphosis compared with the derotation technique from the concave side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Using VCA for Lenke type 1 IS, Vallespir [14] reported that the coronal correction rate was 73.3%, and Yong Qiu [15] described a coronal correction rate of 71.8%. In our study, although a difference was found in the correction rate of the major curve between the bilateral apical vertebral derotation technique by VCM (84.8%) compared with the VCA technique (78.4%), the coronal correction rates in both groups were satisfactory and higher than the average level reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using VCA for Lenke type 1 IS, Vallespir [14] reported that the coronal correction rate was 73.3%, and Yong Qiu [15] described a coronal correction rate of 71.8%. In our study, although a difference was found in the correction rate of the major curve between the bilateral apical vertebral derotation technique by VCM (84.8%) compared with the VCA technique (78.4%), the coronal correction rates in both groups were satisfactory and higher than the average level reported.…”
Section: Discussionmentioning
confidence: 99%
“…Vertebral coplanar alignment (VCA) was described by Vallespir [14] who utilized the coplanar nature of the x - and z- axes of the spine to correct translation and rotation in patients with scoliosis. Clinical studies have demonstrated the effectiveness of 3D correction for IS using VCA [14,15]. However, few reports to date have compared the bilateral apical vertebral derotation technique by VCM to the VCA technique as assessed by radiographic, functional, and outcome parameters, and technical features in patients with IS.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, for this group of patients, earlier surgical correction should be considered with the objective to restore thoracic kyphosis. Several techniques have been introduced for the correction of thoracic kyphosis, including meticulous facetectomy for spinal column release, surgery with a higher implant density and a pedicle screw system, and the vertebral coplanar alignment method [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a portion of articles in our literature review described rod rotation and translation primarily from the concave side[ 2 , 3 , 15 ] or primary use of distracting forces. [ 7 , 10 , 12 ] These techniques, which may be routinely employed in surgical correction of idiopathic scoliosis,[ 9 , 13 , 17 , 18 ] may not be as safe for surgical correction of SDCIP. [ 3 , 18 ] We believe that in the setting of abnormal expansile intraspinal pathology, such as residual low-grade glioma or syringomyelia as in the present case, applying distracting forces [ Figure 6 ] as the primary maneuver for correction of scoliotic spinal deformities may pose potential neurovascular risks.…”
Section: Discussionmentioning
confidence: 99%